Total Synthesis and Comparative Evaluation of Luzopeptin A−C and Quinoxapeptin A−C - Boger, Dale L; Ledeboer, Mark W; Kume, Masaharu; Searcey, Mark; Jin, Qing (Journal of the American Chemical Society, 1999)
Full details of the total syntheses of luzopeptin A−C and quinoxapeptin A−C, C 2-symmetric cyclic depsidecapeptides bearing two pendant heterocyclic chromophores, are disclosed and serve to establish the quinoxapeptin relative and absolute configuration. Key elements of the approach include the late-stage introduction of the chromophore and penultimate l-Htp acylation permitting the divergent synthesis of the luzopeptins, quinoxapeptins, and structural analogues from a common advanced intermediate. Symmetrical pentadepsipeptide coupling and macrocyclization of the 32-membered ring conducted at the single secondary amide site provided the common cyclic decadepsipeptide. The convergent preparation of the required pentadepsipeptide with installation of the labile ester in the final coupling was achieved under surprisingly effective racemization-free conditions. The quinoxapeptins were shown to bind to DNA by high-affinity bisintercalation analogous to sandramycin and the luzopeptins. Significant similarities in the DNA binding of sandramycin and luzopeptin A were observed, and these compounds proved distinguishable from the quinoxapeptins, indicating that the structural alterations in the chromophore impact the affinity and selectivity more than the changes in the decadepsipeptide. The luzopeptins proved to be more potent cytotoxic agents than the corresponding quinoxapeptin, but the quinoxapeptins proved to be more potent inhibitors of HIV-1 reverse transcriptase. In addition, a well-defined potency order was observed in the cytotoxic assays (A > B > C) in which the distinctions were extraordinarily large, with the removal of each l-Htp acyl substituent resulting in a 100−1000-fold reduction in potency. An equally well-defined but reverse potency order was observed in HIV-1 reverse transcriptase inhibition (C > B > A). Thus, the non-naturally occurring synthetic precursor 6 (quinoxapeptin C) was found to exhibit the most potent HIV-1 reverse transcriptase inhibition in the series and to lack a dose-limiting in vitro cytotoxic activity, making it the most attractive member of the series examined.